Experimental evaluation of new one-chip solution for induction motor drives - Araújo, Rui Esteves (2010)
The design of high performance induction motor drives is a complex task, and the every day compelling requirements in energy efficiency and performance assumes the motivation on finding a more integrated solution on implementing induction motor control. The main subjects of this paper are two: to discuss the IFOC one-chip solution and to explore the development of simple graphical applications in order to operate this control in a simple and effective way. Experimental results are presented to illustrate the main points of our paper.